Modeling and Dynamics Characteristic Analysis of Helical Gear System with Considering Tooth Surface Friction - Kang Boqiang; Gou Xiangfeng (Jixie chuandong)
In order to study the dynamics characteristic of the helical gear,according to the situation of helical gear pair in the process transmission,a 5- degree bending- torsion- shaft coupled dynamics model of single- stage helical gear transmission system is established with time- vary friction force. According to the influence of contact ratio,the meshing time is divided. Based on Buckingham semi- empirical formula,the tooth surface friction coefficient variation with the meshing- point position is obtained. The movement differential equations are discussed by the variable step size Runge- Kutta method. The bifurcation diagrams,Lyapunov exponents,cloud pictures of the maximum amplitude and the amplitude- frequency characteristic superposition graphs are obtained and the system dynamics characteristic variation with frequency is analyzed. The strong resonance and amplitude jump phenomenon are happened under the conditions of a particular parameter.